Identification of Key Players Involved in CoCl2 Hypoxia Induced Pulmonary Artery Hypertension in vitro - Chen, Shu; Xu, Hui; Hu, Fen; Wang, Tao (Frontiers in Genetics, 2020)
Background: The proliferation of human pulmonary artery smooth muscle cells (HPASMCs) induced by hypoxia was considered as the main cause of pulmonary arterial hypertension (PAH). This study aimed to explore potential genes and long non-coding RNAs (lncRNAs) involved in the mechanism of hypoxia-induced PAH. Methods: CoCl2 was utilized to induce hypoxia in HPASMCs, and then cell proliferation, apoptosis and expression of hypoxia inducible factors (HIF)-1α were determined. Meanwhile, the RNA isolated from CoCl2-treated cells and control cells were sequenced and differentially expressed genes/lncRNA (DEGs/DELs) were screened followed by protein-protein interaction (PPI) construction, functional enrichment analyses, and lncRNA-target prediction. Finally, the expression of key genes and lncRNAs were were validated using quantitative real-time PCR and western blotting. Results: CoCl2 treatment could significantly increase the expression of HIF-1α and the proliferation of HPASMCs. Total 360 DEGs and 57 DELs were identified between CoCl2 treated and control cells. Functional enrichment analysis showed that up-regulated DEGs and DELs’ targets, including LDHA, PFKP and VEGFA, were significantly enriched in hypoxia or oxygen levels related biological processes, and the downregulated DEGs and DELs’ targets were significantly enriched in extracellular matrix related biological processes. In addition, LDHA, PFKP and VEGFA exhibited a strong relationship with miR-100HG and TSPEAR-AS2 in lncRNA-target network. The protein level of LDHA, PFKP and VEGFA were all increased. Conclusions: LDHA, PFKP, VEGFA and lncRNA miR-100HG and TSPEAR-AS2 probably played crucial roles in the pathogenesis of CoCl2 hypoxia-induced-HAP, which might serve as promising therapeutic targets for PAH.